Application of Digital Marketing Strategy Components in Efforts to Increase Income for Small and Medium Enterprises - Yuvita Permata Sari (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2023)
The daily use of the internet has grown. Micro, small, and medium-sized businesses (MSMEs) need to understand this. Digital marketing is one of the marketing channels that SMEs are currently in high demand for to support sales promotions. This development is valued highly as a company marketing tactic used by MSMEs as well. E-business, E-commerce, social media, chat, and even advertising are highly helpful to MSMEs in terms of sales, marketing, and promotion. This study aims to determine the business revenue attained by MSMEs in Makassar City following the use of digital marketing. In this study, a quantitative approach is used, and Google Forms are used to distribute questionnaires and gather data. The SPSS 22 program was used to process the data. According to the study’s findings, digital marketing has a big impact on MSME players’ income in Makassar City. This research demonstrates to micro, small, and medium-sized businesses (MSMEs) how valuable the use of digital media is for managing a company.